Plan de mejora del sistema de PQRSF del área de admisiones de la Corporación universitaria Minuto de Dios sede Villavicencio (2022)
The PQRSF management systems within the organizations are a source of information on the level of satisfaction of the stakeholders with respect to a product or service provided by the organization, during the development of this work it is expected to learn more about the system of requests, complaints, claims, suggestions and congratulations through the perception of customers and employees of the service offered by the Corporación Universitaria Minuto de Dios. The present work corresponds to the improvement proposal made to the university on its handling and management system of the PQRSF, for which a survey was conducted in order to diagnose the current situation in the management and identify the dissatisfaction that users and other stakeholders have, which for this case the students in the response times by the admissions area, subsequently together with the ISO 10002: 2018 standard a gap analysis was made, in order to identify opportunities for improvement. Subsequently, an improvement proposal was made, for which a diagramming and characterization of how the process should be carried out was made, indicators were defined and it was suggested to include the admissions area within the process map, taking into account the quality management system. Key words: Management system, indicator, improvement, satisfaction, process.